2016
DOI: 10.1002/asna.201612429
|View full text |Cite
|
Sign up to set email alerts
|

Chromospheric activity in sunspot light bridges

Abstract: High-resolution filtergrams from Hinode were used to analyse the nature of chromospheric activity over a set of five sunspot light bridges. The broad-band Ca ii H filtergrams depict a variety of phenomena which include large arc-shaped brightenings, bright patches, and small-scale jets. These strong brightenings are recurrent over a duration of several hours and appear to be a common attribute of a sunspot light bridge, independent of its photospheric morphology and horizontal flow pattern. Hinode spectro-pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…If the homologous nature of the flares were the result of small-scale loops emerging in the LB and reconnecting with the overlying umbral field (Tian et al 2018), one would expect blue-shifts either in localized patches or along the body of the LB (Louis et al 2020). With HMI's native spatial resolution of ∼320 km, we do not find evidence for opposite-polarity fields above uncertainties within the LB, though we do not exclude the possibility of smallscale velocity and magnetic inhomogeneities having been present (Louis et al 2009(Louis et al , 2015aLouis 2015).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…If the homologous nature of the flares were the result of small-scale loops emerging in the LB and reconnecting with the overlying umbral field (Tian et al 2018), one would expect blue-shifts either in localized patches or along the body of the LB (Louis et al 2020). With HMI's native spatial resolution of ∼320 km, we do not find evidence for opposite-polarity fields above uncertainties within the LB, though we do not exclude the possibility of smallscale velocity and magnetic inhomogeneities having been present (Louis et al 2009(Louis et al , 2015aLouis 2015).…”
Section: Discussioncontrasting
confidence: 65%
“…The small-scale jets originating from LBs reported so far exhibited characteristic plasma temperatures below 0.1 MK (Robustini et al 2016;Tian et al 2018) and the general notion is that the jets occur as a result of magnetic reconnection between the overlying umbral field with either emerging bipoles in the LB or with the twisted flux tube comprising the LB (Shimizu et al 2009). However this is at odds with most spectropolarimetric observations with exceptions as seen in Louis (2015). Louis et al (2015a) reported the emergence of a small-scale, flat Ω-loop in a LB.…”
Section: Introductionmentioning
confidence: 91%
“…Such a stressed magnetic topology in LBs has often been cited as the driver for a number of reconnectionassociated phenomena such as small-scale jets (Louis et al 2014;Tian et al 2018), surges (Roy 1973;Asai et al 2001;Toriumi et al 2015;Robustini et al 2016), strong brightenings and/or ejections (Louis et al 2008;Shimizu et al 2009;Louis et al 2009), as well as flares (Berger & Berdyugina 2003;Louis & Thalmann 2021). Enhanced chromospheric activity, which is primarily transient in nature, appears to be an important characteristic of LBs (Louis 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Such a stressed magnetic topology in LBs has often been cited as the driver for a number of reconnection-associated phenomena such as small-scale jets (Louis et al 2014;Tian et al 2018), surges (Roy 1973;Asai et al 2001;Toriumi et al 2015;Robustini et al 2016), strong brightenings and/or ejections (Louis et al 2008;Shimizu et al 2009;Louis et al 2009), as well as flares (Berger & Berdyugina 2003;Louis & Thalmann 2021). Enhanced chromospheric activity, which is primarily transient in nature, appears to be an important characteristic of LBs (Louis 2016).…”
Section: Introductionmentioning
confidence: 99%